2018
DOI: 10.1016/j.cmi.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Electronic clinical decision algorithms for the integrated primary care management of febrile children in low-resource settings: review of existing tools

Abstract: eCDAs are valuable tools that have the potential to improve management of febrile children in primary care and increase the rational use of diagnostics and antimicrobials. Next steps in the evidence pathway should be larger effectiveness and impact studies (including cost analysis) and continuous integration of clinically useful diagnostic and treatment innovations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 30 publications
0
64
1
2
Order By: Relevance
“…Thus, even though our study did not show a risk of missing a serious infection, diagnostic sensitivity of parasite detection must still be adapted to clinical relevance (i.e., there is a need to define parasitemic thresholds to guide clinicians on whether the detected parasites are likely to be symptomatic and/or a risk for community transmission). More importantly, training and guidance to clinicians should be provided to help manage febrile patients in an integrated way, through the provision of (electronic) evidence-based algorithms and guidelines [ 32 ]. Indeed, in this study, clinicians strictly followed electronic algorithms, which are not yet widely available elsewhere and may have helped avoid missing serious infections.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even though our study did not show a risk of missing a serious infection, diagnostic sensitivity of parasite detection must still be adapted to clinical relevance (i.e., there is a need to define parasitemic thresholds to guide clinicians on whether the detected parasites are likely to be symptomatic and/or a risk for community transmission). More importantly, training and guidance to clinicians should be provided to help manage febrile patients in an integrated way, through the provision of (electronic) evidence-based algorithms and guidelines [ 32 ]. Indeed, in this study, clinicians strictly followed electronic algorithms, which are not yet widely available elsewhere and may have helped avoid missing serious infections.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on CDSS for the management of infectious diseases in LMICs and in particular in West Africa. A recent review identified 6 CDSS for the management of febrile children in primary care in LMICs [ 35 ]. In a pilot cluster-randomized controlled study, the clinical algorithm for management of childhood illness available on smartphones (e-ALMANACH) increased the number of children screened for red flags and decreased antibiotic prescription in Tanzania [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under the assumption that only a minority of patients at the primary health care level require antibiotics, CRP/PCT testing was restricted to children with severity indicators and was used to rule in the need for antibiotics. An impressive reduction of antibiotic use was demonstrated in the interventional arm (11.5% compared with 94.9% in routine care) in this study setting, with a trend to lower mortality [ 6 , 23 ].…”
Section: Evidence Base In Sub-saharan Africamentioning
confidence: 99%